PROSPECTS OF STANDARDIZATION AND SYSTEMATIZATION OF THE POINTS FOR EPIZOOTIOLOGICAL SURVEILLANCE OF NATURAL PLAGUE FOCI - A. A. Kuznetsov; S. M. Golosovsky; A. N. Matrosov; A. M. Porshakov; A. A. Lopatin (Проблемы особо опасных инфекций, 2017)
Currently existent procedure for free positioning and registration of sites for field sample collection results in chaotic concentration of visualized on electronic map icons of surveyed areas, which obstructs spatial analysis of the results on monitoring in a given period of time.Objective of the study is to develop the system of standardization, positioning, and numbering of the points for epizootiological surveillance as part of monitoring over natural plague foci.Materials and methods. Topographical maps, epizootiological mapping data and their analysis.Results and conclusions. Optimum size of the icons corresponding to sites of epizootiological surveillance (SES) is 10 seconds in latitude and 15 seconds in longitude. One sector comprises 900 standard SESs. Put forward system of optimization is able to significantly ease epizootiological and epidemiological mapping, enhance visualization of monitoring data, as well as expand the capacities and improve the quality of spatial and retrospective analysis of epizootic activity of natural plague foci.